Sight reduction tables for air navigation selected stars EPOCH 2015 (good through year 2019) (H.O. pub, 2012)
These tables were designed for air navigation where weight and space are at a premium, however, they are very popular with sailors too due to the fact that Vol. 1 offers a speedier way to compute stars. The way the 6 volumes of 229 were combined into this 3 volume set is this: volumes 2 & 3 cover all latitudes, but work only for declinations from 0° to 29° north or south. This covers the sun, moon, planets, and only those stars whose declinations fall into this range. Volume 1 contains some stars (whose declinations may be more than 29°) that are pre-selected for optimum viewing and direction. This volume is applicable for an 8 year period, centered on its Epoch date